Financialization: what it is and why it matters - Thomas I. Palley (Levy Economics Institute of Bard College, 2007)
Financialization is a process whereby financial markets, financial institutions, and financial elites gain greater influence over economic policy and economic outcomes. Financialization transforms the functioning of economic systems at both the macro and micro levels. Its principal impacts are to (1) elevate the significance of the financial sector relative to the real sector, (2) transfer income from the real sector to the financial sector, and (3) increase income inequality and contribute to wage stagnation. Additionally, there are reasons to believe that financialization may put the economy at risk of debt deflation and prolonged recession. Financialization operates through three different conduits: changes in the structure and operation of financial markets, changes in the behavior of nonfinancial corporations, and changes in economic policy. Countering financialization calls for a multifaceted agenda that (1) restores policy control over financial markets, (2) challenges the neoliberal economic policy paradigm encouraged by financialization, (3) makes corporations responsive to interests of stakeholders other than just financial markets, and (4) reforms the political process so as to diminish the influence of corporations and wealthy elites.
Keywords: B50; E44; E60; 330; Financialization; Neoliberal Policy; Deregulation; Debt; Financial Fragility; Finanzkapital; Finanzsektor; Finanzmarkt; Schulden; Makroökonomischer Einfluss; Funktionelle Einkommensverteilung; USA